Real wages and hours in the Great Recession: evidence from firms and their entry-level jobs - Schaefer, Daniel; Singleton, Carl (Munich, 2017)
"Using employer-employee panel data, we provide novel facts on how real wages and working hours within jobs responded to the UK’s Great Recession. In contrast to previous studies, our data enables us to address the cyclical composition of jobs. We show that firms were able to respond to the Great Recession with substantial real wage cuts and by recruiting more part-time workers. A one percentage point increase in the unemployment rate led to an average decline in real hourly wages of 2.8 per cent for new hires and 2.6 per cent for job stayers. Hours of new hires in entry-level jobs were also substantially procyclical, while job-stayer hours were nearly constant. Our findings suggest that models assuming rigid labour costs of new hires are not helpful for understanding the behaviour of unemployment over the business cycle."